HISTORICAL DEVELOPMENT OF ALEVISM AND BEKTASHISM - YILDIRIM, Burcu Erdem; TANSÜ, Yunus Emre (SSD Journal, 2018)
The Alewi-Bektashi population, being an important and radical section of the social structure within the states of the Seldjuks, Ottomans and modern Turkey, have through their history always tried to express themselves. This expression could from time to time take the form of rebellion against the central authority, but also the form of oral and written litterary and intellectual outcome. As one of the key fellows of the Alewi-Bektashi tradition, Kaygusuz Baba (Abdal) is an important poet, a poet expressing and explaining the social environment within that same tradition. In his work ‘Budalanâme’, a work rich of information about the ways and beliefs of Alewi- Bektashis, he tells us about the path to God. This is a work which gives ample information about Religious Order (Tariqa) and benefitting knowledge to its followers, a work enforced with different Hadith and Ayah from the Holy Qoran. The work gives also ample information about the lives of prophets and other historical figures.